Changing Spaces: The Evidence of Vienne - Wood, Ian (Reti Medievali Rivista, 2023)
The evidence for the city of Vienne allows us to reconstruct the transformation of what had been a provincial capital of the Roman Empire, into a city dominated by the Church, initially, in the late fifth century, following the reaction of bishop Mamertus to a major earthquake, and subsequently as a result of the foundation of monasteries, some of which were in existence by the end of the fifth century, but the majority of which were founded in the sixth and seventh.